Pengaruh Return on Asset (ROA), Return on Equity (ROE), dan Net Profit Margin (NPM) terhadap Harga Saham pada PT Astra Otoparts Tbk Periode 2017–2023 - Naufal Bintang Azhar; Guyub Nuryanto; Rooswhan Budhi Utomo; Arncliffe Joya; Assyifa Fauziah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The automotive component industry plays an important role in supporting economic growth and industrial development in Indonesia. The financial performance of a company is one of the factors considered by investors in assessing investment decisions, particularly through profitability indicators such as Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM), which may influence stock price movements. This study aims to analyze the effect of ROA, ROE, and NPM on the stock price of PT Astra Otoparts Tbk during the 2017–2023 period. This research employed a quantitative approach using secondary data obtained from the annual financial reports of PT Astra Otoparts Tbk and stock price data from the Indonesia Stock Exchange (IDX) and Stockbit application. The population in this study consisted of all financial report data and stock price data of PT Astra Otoparts Tbk. The sample was determined using a purposive sampling technique, with the selected sample consisting of financial data and closing stock prices for the 2017–2023 period. Data analysis was conducted using SPSS version 30, including classical assumption tests, multiple linear regression analysis, partial t-tests, simultaneous F-tests, and the coefficient of determination (R²). The results indicate that ROA, ROE, and NPM partially and simultaneously have a significant effect on the stock price of PT Astra Otoparts Tbk. These findings emphasize the importance of profitability performance as a consideration for investors and corporate management in evaluating financial and investment decisions.